Prognostic value of pre-treatment F-18-FDG PET-CT in patients with hepatocellular carcinoma undergoing radioembolization - Abuodeh, Yazan; Naghavi, Arash O; Ahmed, Kamran A; Venkat, Puja S; Kim, Youngchul; Kis, Bela; Choi, Junsung; Biebel, Benjamin; Sweeney, Jennifer; Anaya, Daniel A; Kim, Richard; Malafa, Mokenge; et al. (World journal of gastroenterology : WJG, 2016)
AIM To evaluate the value of pre-treatment 18F-FDG PET/CT in patients with HCC following liver radioembolization.METHODS We identified 34 patients with HCC who underwent an FDG PET/CT scan prior to hepatic radioembolization at our institution between 2009 and 2013. Patients wereseen in clinic one month after radioembolization and then at 2-3 mo intervals. We assessed the influence of FDG tumor uptake on outcomes including local liver control(LLC), distant liver control(DLC), time to distant metastases(DM), progression free survival(PFS) and overall survival(OS).RESULTS The majority of patients were males(n = 25, 74%), and had Child Pugh Class A(n = 31, 91%), with a median age of 68 years(46-84 years). FDG-avid disease was found in 19(56%) patients with SUVmax ranging from 3 to 20. Female patients were more likely to have an FDG-avid HCC(P = 0.02). Median follow up of patients following radioembolization was 12 months(1.2-62.8 mo). FDG-avid disease was associated with a decreased 1 year LLC, DLC, DM and PFS(P < 0.05). Using multivariate analysis, FDG avidity predicted for LLC, DLC, and PFS(all P < 0.05).CONCLUSION In this retrospective study, pre-treatment HCC FDGavidity was found to be associated with worse LLC, DLC, and PFS following radioembolization. Larger studies are needed to validate our initial findings to assess the role of F-18-FDG PET/CT scans as biomarker for patients with HCC following radioembolization.